The burlesque handbook - Weldon, Jo. (New York : It! Books, 2010)
'From one of the stars of the newly popular burlesque scene comes a definitive, easy-to-use, and indispensable guide to the art form, with a foreword by superstar comedian and burlesque enthusiast Margaret Cho'--
Keywords: Striptease; Burlesque (Theater)